Pharmacist-Delivered Patient Care in an Interdisciplinary Team-Based Institutional Palliative Care Clinic, 2012 to 2018. Issue 3 (July 2021) - Dayer, Lindsey E.; McDade, Elizabeth R.; Harrington, Sarah
Palliative care services offered in the United States have grown substantially since the year 2000. These types of services have been shown to improve a patient's quality of life when presented with a serious or life-threatening disease or illness. An important characteristic of a quality palliative care service is the presence of an interdisciplinary team to utilize different areas of expertise to address multiple aspects of patient care. An important member of this team is the pharmacist. The services presented in this interprofessional education and practice guide describe pharmacist-delivered palliative care services offered in an institutional ambulatory palliative care setting from 2012 to 2018.